Susceptibility of Vibrio aestuarianus 01/032 to the antibacterial activity of Mytilus haemolymph: Identification of a serum opsonin involved in mannose-sensitive interactions - PEZZATI, ELISABETTA; CANESI, LAURA; DAMONTE, GIANLUCA; SALIS, ANNALISA; MARSANO, FRANCESCO; GRANDE, CHIARA; VEZZULLI, LUIGI; PRUZZO, CARLA (Environmental Microbiology, 2015)
The interactions of Vibrio aestuarianus 01/032 with haemolymph of the bivalves Mytilus galloprovincialis and Crassostrea gigas were investigated to understand if haemolymph components (haemocytes and soluble factors) could be involved in the higher resistance to microbial infection shown by mussels in comparison with oysters. Although 01/032 bacteria adhered to haemocytes of both bivalves, they were sensitive to the bactericidal activity of whole haemolymph from mussel, but not from oyster; in addition, adhesion to mussel (but not oyster) haemocytes was affected by D-mannose. Mussel serum opsonins directed towards D-mannose-binding bacterial ligands were purified by affinity chromatography and were shown to mediate 01/032 interactions with M.galloprovincialis haemocytes. Nano-High Performance Liquid Chromatography-Electrospray Ionization-Tandem Mass Spectrometry (HPLC-ESI-MS/MS) analysis showed that the purified opsonin matched the protein precursor of Mytilus edulis extrapallial protein (EP). In the presence of M.galloprovincialisEP protein (MgEP), C.gigas haemocytes killed V.aestuarianus 01/032 almost as efficiently as mussel phagocytes. These findings suggest that the different sensitivity of 01/032 strain to the antibacterial activity of oyster and mussel haemolymph might partly depend on the fact that C.gigas serum lacks MgEP-like opsonins. These results represent the basis for understanding the different sensitivity to microbial infections shown by the two bivalve species.